2011
DOI: 10.1107/s1744309111004349
|View full text |Cite
|
Sign up to set email alerts
|

Structures of phosphopantetheine adenylyltransferase fromBurkholderia pseudomallei

Abstract: PDB References: PPAT, 3pxu; 3k9w.Phosphopantetheine adenylyltransferase (PPAT) catalyzes the fourth of five steps in the coenzyme A biosynthetic pathway, reversibly transferring an adenylyl group from ATP onto 4 0 -phosphopantetheine to yield dephosphocoenzyme A and pyrophosphate. Burkholderia pseudomallei is a soil-and waterborne pathogenic bacterium and the etiologic agent of melioidosis, a potentially fatal systemic disease present in southeast Asia. Two crystal structures are presented of the PPAT from B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The electron density corresponding to the adenosine nucleotide of pCC is ambiguous, indicative of disorder because of the minimal interactions of this moiety with the protein and its residence within a solvent pocket in the crystal lattice. Similar disorder has been observed for the adenosine group in other CoA-bound structures (20,21). These cross-subunit interactions with the pCC ligand result in an inward constriction of the second subunit upon binding of the ligand to the first subunit ( Fig.…”
Section: Structural Basis For Regulation Of Coumarate Catabolismsupporting
confidence: 76%
“…The electron density corresponding to the adenosine nucleotide of pCC is ambiguous, indicative of disorder because of the minimal interactions of this moiety with the protein and its residence within a solvent pocket in the crystal lattice. Similar disorder has been observed for the adenosine group in other CoA-bound structures (20,21). These cross-subunit interactions with the pCC ligand result in an inward constriction of the second subunit upon binding of the ligand to the first subunit ( Fig.…”
Section: Structural Basis For Regulation Of Coumarate Catabolismsupporting
confidence: 76%
“…For the forward reaction inorganic pyrophosphate was quantified using the Malachite green method. A 5 μM aliquot of dialyzed enzyme was incubated either with variable concentration of 4' -phosphopantetheine or PhP (3,10,15,20,25,30,35,40,60, 100, 125μM), a fixed concentration (100 μM) of adenosine triphosphate (ATP), or a fixed concentration of PhP and with variable concentration of ATP. The reaction was carried out in 50 mM HEPES pH 7.0, 200 mM NaCl and 5 mM MgCl 2 at 25°C.…”
Section: Forward Steady-state Kinetic Assaymentioning
confidence: 99%
“…Till date, a number of PPAT X-ray crystal structures have been solved in various organisms, viz. E. coli with multiple ligands [17,19,24], [29] and Burkholderia pseudomallei in complex with hydrolyzed dPCoA [PDB ID: 3K9W] [30]. In most of the cases the enzyme seemed to form hexamers, except in E. coli, where the enzyme uses Mn 2+ instead of Mg 2+ and is dimeric in nature showing half-site reactivity [17].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the three-dimensional structures of apo PPAT and of PPAT complexed with several functional ligands (ATP, CoA, dPCoA and PhP) have been solved for a number of bacterial enzymes. They have been most thoroughly studied for PPAT from Escherichia coli (PPATEc) and PPAT from M. tuberculosis (PPATMt), which have a high degree of homology to each other Badger et al, 2005;Takahashi et al, 2004;Edwards et al, 2011;Yoon et al, 2011;Timofeev et al, 2010Timofeev et al, , 2012. The degree of identity between these enzymes is 44% and their similarity is about 77% (Timofeev et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the biologically active form of all known bacterial PPATs is a homohexamer with point symmetry 32 composed of two trimers (Takahashi et al, 2004;Badger et al, 2005;Yoon et al, 2011;Edwards et al, 2011). Each subunit of PPATMt contains 161 amino-acid residues.…”
Section: Introductionmentioning
confidence: 99%